2002
DOI: 10.1051/0004-6361:20020044
|View full text |Cite
|
Sign up to set email alerts
|

Global static electrospheres of charged pulsars

Abstract: Abstract. In this paper we present self-consistent models of the magnetosphere of inactive, charged, aligned rotator pulsars. We have devised an efficient semi-analytical and numerical algorithm to construct such models. The only free parameter is the total charge of the system. These charge-separated "electrospheres" consist of an equatorial belt carrying charge of one sign, partially in differential rotation, and of two oppositely charged domes located over the poles which corotate with the neutron star. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 37 publications
8
68
0
Order By: Relevance
“…later found to develop a diocotron instability (see Figure 9b) [139,137], which led to cross field diffusion of the particles and partial filling of the magnetosphere, but not out to the light cylinder [140]. A PIC simulation of the electrosphere [141] showed that the diocotron instability developed even faster for an inclined rotator, filling the magnetosphere out to the light cylinder, but for computational reasons the simulation was limited in time and number of particles.…”
Section: N-body and Particle-in-cell Magnetosphere Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…later found to develop a diocotron instability (see Figure 9b) [139,137], which led to cross field diffusion of the particles and partial filling of the magnetosphere, but not out to the light cylinder [140]. A PIC simulation of the electrosphere [141] showed that the diocotron instability developed even faster for an inclined rotator, filling the magnetosphere out to the light cylinder, but for computational reasons the simulation was limited in time and number of particles.…”
Section: N-body and Particle-in-cell Magnetosphere Modelsmentioning
confidence: 99%
“…Arrows are magnetic field lines and color is sign of charge: red for positrons, blue for electrons. Right: diocotron instability in the equatorial plane of a charge-separated aligned rotator [137], showing density perturbations (color) and velocity field (arrows).later found to develop a diocotron instability (see Figure 9b) [139,137], which led to cross field diffusion of the particles and partial filling of the magnetosphere, but not out to the light cylinder [140]. A PIC simulation of the electrosphere [141] showed that the diocotron instability developed even faster for an inclined rotator, filling the magnetosphere out to the light cylinder, but for computational reasons the simulation was limited in time and number of particles.…”
mentioning
confidence: 99%
“…current closure, remains with the primary particles. Static pulsar electrospheres (Pétri et al 2002b) are models that do not involve charge circulation. Unfortunately, they do not create a wind either, and they are not expected to radiate.…”
Section: A Pulsar That Extracts Electrons From One Pole and Protons Fmentioning
confidence: 99%
“…Another dyadic pair could be a dead, "electrosphere" state (e.g., Michel 1980;Krause-Polstorff & Michel 1985;Michel 1991;Smith et al 2001;Pétri et al 2002) versus a standard, dynamic magnetosphere. Extreme switching between an electrosphere and a magnetosphere might be associated with the more extreme RRATs and long-term intermittent objects (e.g., Michel 2010).…”
Section: Metastable Statesmentioning
confidence: 99%